Advanced airway management in an anaesthesiologist-staffed Helicopter Emergency Medical Service (HEMS): A retrospective analysis of 1047 out-of-hospital intubations. (August 2016) - Piegeler, Tobias; Neth, Philippe; Schlaepfer, Martin; Sulser, Simon; Albrecht, Roland; Seifert, Burkhardt; Spahn, Donat R.; Ruetzler, Kurt
Abstract: Introduction: Airway management in the out-of-hospital emergency setting is challenging. Failed and even prolonged airway management is associated with serious clinical consequences, such as desaturation, bradycardia, airway injuries, or aspiration. The overall success rate of tracheal intubation ranges between 77% and 99%, depending on the level of experience of the provider. Therefore, advanced airway management should only be performed by highly-skilled and experienced providers. Methods: 9765 patients were treated in the out-of-hospital emergency setting by the anaesthesiologist-staffed Helicopter Emergency Medical Services (HEMS) between 2002 and 2014. Patients successfully intubated upon the first attempt were compared to patients who required more than one intubation attempts regarding several potential confounding factors such as age, gender, on-going CPR, NACA Score, initial GCS, prior administration of anaesthetic drugs, neuromuscular blocking agents, and vasopressors. Results: 1573 out of 9765 patients (16.1%) required advanced airway management. 459 patients had already been intubated upon arrival of the HEMS, whereas 1114 patients (11.4%) underwent advanced airway management by the HEMS physician. 67 patients had to be excluded. Data for the remaining 1047 patients (790 males and 257 females) were analyzed further. Primary use of an alternative airway device was reported in 59 patients (5.6%), whereas 988 patients (94.4%) underwent laryngoscopy-guided tracheal intubation. 952 patients (96.4%) could be intubated upon the first attempt and overall intubation success was 99.5% (983 out of 988). Conclusion: Our study demonstrates that HEMS physicians performed airway management frequently and that both the first attempt as well as the overall success rate of tracheal intubation was high. Together with the fact that all failed and difficult intubations were successfully recognized and handled and that no surgical airway had to be established, the current study once more underlines the importance of proper training of HEMS care providers regarding airway management.